Mini-Publics and Party Ideology: Who Commissioned the Deliberative Wave in Europe? - Rodrigo Ramis-Moyano; Graham Smith; Ernesto Ganuza; Thamy Pogrebinschi (Journal of Deliberative Democracy, 2025)
The increasing implementation of deliberative mini-publics (DMPs) such as Citizens' Assemblies and Citizens' Juries led the OECD to identify a `deliberative wave'. The burgeoning scholarship on DMPs has increased understanding of how they operate and their impact, but less attention has been paid to the drivers behind this diffusion. Existing research on democratic innovations has underlined the role of the governing party's ideology as a relevant variable in the study of the adoption of other procedures such as participatory budgeting, placing left-wing parties as a prominent actor in this process. Unlike this previous literature, we have little understanding of whether mini-publics appeal equally across the ideological spectrum. This paper draws on the large-N OECD database to analyse the impact of governing party affiliation on the commissioning of DMPs in Europe across the last four decades. Our analysis finds the ideological pattern of adoption is less clear cut compared to other democratic innovations such as participatory budgeting. But stronger ideological differentiation emerges when we pay close attention to the design features of DMPs implemented.
Keywords: 320; Deliberative mini-publics; Political parties; Ideology; Europe; Citizens' assemblies